Pengembangan Sumber Daya Manusia dalam Pengelolaan Ekonomi Kreatif di Masa Pandemi COVID-19 di Masyarakat Desa Tafure dan Sulamadaha Kota Ternate: Human Resource Development in Managing the Creative Economy during the COVID-19 Pandemic in the Community of Tafure and Sulamadaha Village, Ternate City. - Nurlaila Nurlaila (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
This study aims to provide an in-depth overview of the application of the creative economy during the COVID-19 pandemic to increase economic income. Human Management Resources in an organization are not just administrative but lead to developing the potential of human resources to be creative and innovative. A creative economy is an economic concept combining something with an element of creativity by combining ideas, ideas, and knowledge from human resources as a production factor. The condition of the COVID-19 pandemic is very unsettling for the community. Therefore it requires skills and the desire of business actors to develop a creative economy. The research uses a descriptive qualitative approach with respondents, samples from the Tafure community and the Sulamadaha community, respectively, as many as four people who have a business with key informants from the local community who have had a business for 8 and 10 years. Retrieval data in the form of observations and interviews with eight people consisting of 6 field informants and two key informants. The data collection technique uses triangulation in which researchers compare information from the field with information and data from informants, both field informants and key informants, with conditions in the local area. Research data analysis is inductive; some data and information are obtained and then developed into a hypothesis. The COVID-19 pandemic has made the economic life of a business very impactful on people’s financial income. Tafure community business actors have implemented creative economy human resource development through participation in education and training activities.